Does gastrostomy tube feeding in children with cerebral palsy increase the risk of respiratory morbidity? - Sullivan, P; Morrice, J; Vernon-Roberts, A; Grant, H; Eltumi, M; Thomas, A (2006)
BACKGROUND: Children with severe neurological impairment may have significant oral motor dysfunction and are at increased risk of nutritional deficiencies, poor growth, and aspiration pneumonia. Gastrostomy tube feeding is increasingly being used for nutritional support in these children. AIM: To examine the occurrence of respiratory morbidity before and after gastrostomy feeding tube insertion in children with severe neurological disabilities. METHODS: This study was nested in a longitudinal, prospective, uncontrolled, multicentre cohort study designed to investigate the outcomes of gastrostomy tube feeding in 57 children with severe neurological disabilities. Parents completed a questionnaire prior to (visit 1) and 6 and 12 months (visits 2 and 3) following the gastrostomy, detailing number of chest infections requiring antibiotics and/or hospital admission. RESULTS: Mean number of chest infections requiring antibiotics was 1.8 on visit 1 and 0.9 on visit 3. Hospital admissions for chest infections fell significantly from 0.5 to 0.09. CONCLUSION: This study provides no evidence for an increase in respiratory morbidity following insertion of a feeding gastrostomy in children with cerebral palsy.